Effects of arts-integrated socio-scientific inquiry-based instruction on students' environmental stewardship and scientific creativity - Galano, Jasmin S.
Industrialization has caused fast-changing environmental conditions which makes it crucial to develop methods that can help individuals become responsive problem-solvers in this concern. While science education seeks to develop scientifically literate individuals, arts integration engages students in a creative process that allows them to express themselves. As a response, this study aimed to determine the effect of Arts-Integrated Socio-Scientific Inquiry-Based Instruction (ASII) on students’ environmental stewardship and scientific creativity and to identify the extent of the relationship between environmental stewardship and scientific creativity through a quasi-experimental research design. The Environmental Stewardship Scale (ESS) and Scientific Creativity Test (SCT), attained a Cronbach’s alpha value of .95 and .98, respectively, with an Inter-Item Correlation coefficient for SCT ranging from .93-.97 and an Intraclass Correlation coefficient of .98 for Average Measures. The study was conducted in a private school in Bulacan, Philippines, where ASII and Conventional Instruction (CI) received five cycles/lessons in Earth and Space Science. As a result, although ASII did not perform significantly better than CI in terms of environmental stewardship (p = .066) and it is only in the subcategory of Institutional Capital where CI performed better than ASII (p = .038), ASII improved significantly on the subcategories of Overall capital (p = .045), Cultural capital (.002), and Human Capital (.017) while CI showed significant improvement on Overall Capital (p = .006), Human Capital (.009), and Social Capital (p = .010). In terms of scientific creativity, ASII performed significantly better than CI (p = .000). Lastly, it was observed that there is no significant relationship between environmental stewardship and scientific creativity (r = .016, n = 67, p = .450). This implies that learners can create deeper connections to their surroundings through student-led inquiries, but they can also increase their social capital when provided an opportunity to interact. Enhancing students’ scientific creativity may also necessitate learning environments that promote it. Finally, in addition to scientific creativity, it would be advantageous to investigate other forms of creativity that may indicate students’ abilities to address issues in environmentally friendly ways.